Does Marketing System Influence on Consumer Satisfaction?: Study of Marine Fish Marketing System at Fish Auction “PPN Muara Angke”, North Jakarta - Zainal Abidin; Melati Meitasari (Faculty of Fisheries and Marine Science, Brawijaya University, 2019)
Market performance in the form of marketing efficiency is the result of a good marketing system which then affects consumer satisfaction. This research was conducted to analyze: 1) satisfaction of marine fish consumers at fish auction PPN Muara Angke, 2) influence of market performance on consumer satisfaction, 3) differences in marketing efficiency between fishermen and traders, 4) differences in satisfaction of fishermen and merchant’s consumers. The research method used is a qualitative and quantitative descriptive research type. The population in this study are ship owners or fishermen, auction participants which include wholesalers, wholesalers, processors, and retail traders. Sample determination technique using purposive sampling and snowball sampling with a sample of 42 people. The analysis technique used is descriptive, simple linear regression, and one-way ANOVA real difference test. Based on the results of the study that marine fish consumer satisfaction in Muara Angke it can be said to be satisfied and market performance affects consumer satisfaction. The marketing efficiency of fishermen and traders is equally efficient but more efficient marketing of fishermen and the satisfaction of fishermen and traders are equally satisfying but more satisfied by fishermen consumers.